2003
DOI: 10.1111/j.0909-8836.2003.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐contact removal of coadhering and non‐coadhering bacterial pairs from pellicle surfaces by sonic brushing and de novo adhesion

Abstract: Coadhesion between oral microbial pairs is an established factor in the spatiotemporal development and prevalence of mixed-species communities in early dental plaque in vivo. This study compares removal and de novo adhesion of pairs of coadhering and non-coadhering oral actinomyces and streptococci by sonic brushing on salivary pellicles in a non-contact mode as a function of the distance between the brush and the pellicle surface in vitro. First, actinomycetes were adhered to a pellicle surface, after which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 14 publications
(22 reference statements)
0
38
1
Order By: Relevance
“…Previous data suggesting a potential superiority of sonic toothbrushes [25] could not be confi rmed by our study. The brush head type did not show a signifi cant effect either.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous data suggesting a potential superiority of sonic toothbrushes [25] could not be confi rmed by our study. The brush head type did not show a signifi cant effect either.…”
Section: Discussioncontrasting
confidence: 99%
“…A study by Busscher and co-workers showed that sonic brushing at contact removed 92% to 94% of the coadhering and non-coadhering pair under investigation, respectively, but removal decreased with increasing distance between the brush and the pellicle surfaces [22]. Especially non-contact biofilm removal must be regarded as an interplay of hydrodynamic energy transfer through the fluid [23].…”
Section: Discussionmentioning
confidence: 96%
“…Subsequently, after re-mounting the bottom plate in the flow chamber, it was filled again with buffer and rinsed for 10 min, after which, ten images of the brushed areas were taken. Protocol A was only done for contact brushing, since previous experiments with non-contact brushing have indicated almost full removal of initially adhering bacteria at 2-mm distance [4, 39]. …”
Section: Methodsmentioning
confidence: 99%